A Molecular Dynamics Study of the Effect of Voids on the Deformation Behavior of Nanocrystalline Copper. (15th November 2007) - Zheng, Chen; Zhang, Yong-Wei
Abstract : Molecular dynamics simulations are performed to study the effect of preexisting ellipsoidal voids on the tensile deformation behavior in nanocrystalline copper. No crack propagation is observed regardless of the orientation of the voids with respect to the tensile direction. However it is found that the voids may assist the shear plane formation via (1) emitting dislocations from the void tips, (2) relieving triple-junction confinement, and (3) catalyzing grain splitting.